Successful systemic propranolol treatment for periocular capillary hemangioma in Indonesian infant girls: A case series - Neni Anggraini; Mutmainah (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Capillary hemangioma (CH) is the most prevalent benign tumour in children. Most cases showed spontaneous involution without any intervention. However, approximately 10% of all CH patients require treatment. Most cases of periocular capillary hemangioma (PCH), especially orbital form, risk significant morbidity; therefore, aggressive treatment is needed. Studies showed a superior outcome of systemic propranolol for CH compared to standard therapy (corticosteroids). We present cases with different PCH types successfully treated with systemic propranolol. Five patients with different types of PCH were given systemic propranolol. One patient presented with a lesion at birth, while others were less than ten months of age. Oral propranolol was given at 0.5 mg/kg body weight (BW) as the initial dose for two weeks. The dose was gradually increased to 2.0 mg/kg BW within 1-18 months of treatment. All patients showed sufficient initial responses regarding mass reduction and colour change within 2-12 weeks. No complications or adverse effects were observed. The regimen of 2.0 mg/kg BW systemic propranolol treatment was considered safe and beneficial for PCH.